The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4172/2332-0737.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Plant Growth Promoting Rhizobacteria Associated with Saccharum officinarum L.

Abstract: Plant growth promoting rhizobacteria is free living soil microorganisms that directly or indirectly exert beneficial effects on plants. Hundred strains were characterized morphologically and biochemically. Primary screening was carried out for all hundred isolates for IAA, phosphate solubilization, siderophore and nitrogen fixation. Eight isolates F181, F271, F323, F372, F373, F531, ELB1 and ESB4 from different sites and sugarcane cultivars have showed potential for all PGPR activities and were further investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Although many studies on the PGP activities of the sugarcane rhizobacteria have been reported till date, only a few of them have reported both PGP and biocontrol. In recent years, different rhizobacteria including members of the genus Acinetobacter and Klebsiella have been reported from the sugarcane to possess PGP properties [16,[30], [31], [32]].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies on the PGP activities of the sugarcane rhizobacteria have been reported till date, only a few of them have reported both PGP and biocontrol. In recent years, different rhizobacteria including members of the genus Acinetobacter and Klebsiella have been reported from the sugarcane to possess PGP properties [16,[30], [31], [32]].…”
Section: Discussionmentioning
confidence: 99%
“…Vessey [41] found phosphate-solubilizing rhizobacteria to be one of the finest alternatives to inorganic phosphate fertilizers for improving plant productivity and development since phosphorus has been identified as one of the most critical nutrients for plant growth [69]. According to Modi and Patel [70], the best isolates Bacillus sp., Pantoea sp., Klebsiella sp., Stenotrophomonas sp. and Burkholderia sp.…”
Section: Phosphate Solubilization Abilitymentioning
confidence: 99%
“…Vessey [41] found phosphate-solubilizing rhizobacteria to be one of the finest alternatives to inorganic phosphate fertilizers for improving plant productivity and development since phosphorus has been identified as one of the most critical nutrients for plant growth [69]. According to Modi and Patel [70], the best isolates as phosphate solubilizers were F372 (15 mg/L), which was associated with Saccharum officinarum, followed by ESB4 (14 mg/L). Bhardwaj et al [71] obtained similar consistent phosphate solubilization findings in both agar and broth assays.…”
Section: Phosphate Solubilization Abilitymentioning
confidence: 99%
“…In the same way, microorganisms capable of producing a clear zone due to Phosphate solubilization in the surrounding Pikovskaya medium were selected as potential phosphate solubilizers [41]. Moreover, the results of [42] stated the ability of eight out of 61 rhizobacterial isolates to solubilize phosphate.…”
Section: Isolation and Morphological Characterization Of Rhizobacterial Isolatesmentioning
confidence: 99%